М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
5class1i
5class1i
07.10.2020 13:59 •  Алгебра

Реши систему уравнений методом подстановки.
{−x−2y+1=4
x=−8−y

ответ:
x=
y=

👇
Открыть все ответы
Ответ:
evmenovvlad
evmenovvlad
07.10.2020
A₁ = 5, аn + 1= an + 3
a₂ = 5 + 3 = 8
d = 3
a₁₂ = 5 + 3(12-1) = 5 + 33 = 38
a₃₄ = 5 + 3(34-1) = 5 + 99 = 104

a₁ = 84, d = -5
a₃₇ = 84 - 5(37-1) = -96
a₆₀ = 84 - 5(60-1) = -211

-67; -60; -53...
а₁ = -67
d = 7
S₅₂ = 2a₁ + d(n-1)*n / 2 = 2*(-67) + 7(52-1)*52 / 2 = -134 + 18564 / 2 = 9215

an = 5n - 4
a₁ = 5*1 - 4 = 1
a₂ = 5*2 - 4 = 6
d = 5
S₁₅₀ = 2a₁ + d(n-1)*n / 2 = 2*1 + 5(150-1)*150 / 2 = 2 + 111750 / 2 = 55876

a₁ = 32, а₆₁ = -58
a₆₁ = 32 + d(61-1) = 32 + 60d
-58 = 32 + 60d
60d = -90
d = -1,5
-36 = 32 - 1,5(n-1)
-36 = 32 -1,5n + 1,5 
-36 = 33,5 - 1,5n
-69,5 = 1,5n 
n = -69,5/1,5 - не является

8, 16, 24, 32, 40, 48, 56, 64, 72, 80, 88, 96, 104, 112, 120, 128, 136, 144, 152, 160, 168, 176, 184, 192, 200, 208, 216, 224, 232, 240, 248, 256, 264, 272, 280, 288, 296, 304, 312, 320, 328, 336, 344.
S = 7568
4,4(41 оценок)
Ответ:
ZigFinde
ZigFinde
07.10.2020
1/5*6^1024-[(6^512+1)(6^256+1)(6^128+1)(6^64+1)(6^32+1)(6^16+1)(6^8+1)(6^4+1)(6²+1)(6+1)(6-1)]/(6-1)=1/5*6^1024-1/5[(6^512+1)(6^256+1)(6^128+1)(6^64+1)(6^32+1)(6^16+1)(6^8+1)(6^4+1)(6²+1)(6²-1)]=
=1/5*6^1024-1/5[(6^512+1)(6^256+1)(6^128+1)(6^64+1)(6^32+1)(6^16+1)(6^8+1)(6^4+1)(6^4-1)]=1/5*6^1024-1/5[(6^512+1)(6^256+1)(6^128+1)(6^64+1)(6^32+1)(6^16+1)(6^8+1)(6^8-1)]=1/5*6^1024-1/5[(6^512+1)(6^256+1)(6^128+1)(6^64+1)(6^32+1)(6^16+1)(6^16-1)=1/5*6^1024-1/5[(6^512+1)(6^256+1)(6^128+1)(6^64+1)(6^32+1)(6^32-1)]=1/5*6^1024-1/5[(6^512+1)(6^256+1)(6^128+1)(6^64+1)(6^64-1)]=1/5*6^1024-1/5[(6^512+1)(6^256+1)(6^128+1)(6^128-1)]=1/5*6^1024-1/5[(6^512+1)(6^256+1)(6^256-1)]=1/5*6^1024-1/5[(6^512+1)(6^512-1)]=1/5*6^1024-1/5(6^1024-1)=1/5*6^1024-1/5*6^1024+1/5=0,2
4,7(87 оценок)
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ